Study of laser welding and heat treatments done in different high strength steels: 4340, 300M, maraging 300 - De Souza Martins Cardoso, Andréia; Abdalla, Antonio Jorge; De Lima, Milton Sergio Fernandes; Bonjorni, Felipe Martins; Barboza, Miguel Justino Ribeiro; Baptista, Carlos Antonio Reis Pereira; Fanton, Leonardo [UNESP] (SAE International, 2013)
The medium carbon steel and low alloy SAE 4340 has undergone several changes in this development process came 300M steel, from this ultra-high strength steel. With similar resistance and higher ductility to the steel 300M, the maraging steel can replace conventional steels in various applications. This study aims to evaluate and compare the microstructure and mechanical strength of SAE 4340 steel, 300M and Maraging 18Ni 300, underwent the procedure of autogenous laser welding. © 2013 SAE INTERNATIONAL.